Conservation tourism - Buckley, Ralf, (CABI, 2010)
The principal focus of this book (consisting of 13 chapters) is on the conservation contributions of commercial tourism enterprises. It presents examples and analyses of conservation tourism from around the world, using a range of different mechanisms at a variety of scales, with a focus on models, approaches and cases which seem to have been successful. It starts by presenting four particular companies in detail, and continues with a geographically structured overview which is less detailed but broader in scope.